2011
DOI: 10.1007/s10211-011-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Interference competition and group size effect in sika deer (Cervus nippon) at salt licks

Abstract: Competition has long been considered as a confounding factor of group size effect but the understanding of interference competition is rudimentary for the difficulty in disentangling interference competition from scramble competition adequately. Here, we analysed remote-camera video records of wild sika deer (Cervus nippon) at salt licks in southern China from March 1, 2006 to November 30, 2008 to investigate how interference competition and predation risk interacted on vigilance behaviour. Scramble competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Through altering the timing of foraging activities, species can reduce interspecific contact and thus facilitate temporal niche partitioning (Carothers and Jaksić 1984;Hayward and Slotow 2009). Studies have found that aggression between species can influence individuals to change their behaviours to reduce chance of interactions (Wrobell et al 1980;Ping et al 2011;Barrull et al 2014) though the presence of scent can also mediate changes in behaviour spatially and temporally (Dickman 1991;Mukherjee et al 2009;Leo et al 2015). Our study offers a unique opportunity to investigate this effect of behavioural interference, as aggression and territorial (scent marking) behaviours for select species were observed in our study.…”
Section: Introductionmentioning
confidence: 75%
“…Through altering the timing of foraging activities, species can reduce interspecific contact and thus facilitate temporal niche partitioning (Carothers and Jaksić 1984;Hayward and Slotow 2009). Studies have found that aggression between species can influence individuals to change their behaviours to reduce chance of interactions (Wrobell et al 1980;Ping et al 2011;Barrull et al 2014) though the presence of scent can also mediate changes in behaviour spatially and temporally (Dickman 1991;Mukherjee et al 2009;Leo et al 2015). Our study offers a unique opportunity to investigate this effect of behavioural interference, as aggression and territorial (scent marking) behaviours for select species were observed in our study.…”
Section: Introductionmentioning
confidence: 75%
“…25–35%), sika deer ( Cervus nippon ) in Pengze County, China (Ping et al. ; : c . 20–30%), but see also: Berger & Cunningham ; Laundre et al.…”
Section: Discussionmentioning
confidence: 99%
“…When foraging during daytime, deer were, on average, overtly vigilant c. 14% of the time, which is similar to the levels of overt vigilance (between 10% and 20%) recorded in white-tailed deer on Ossabaw Island (Georgia, USA) where wolves and cougars occur (Lagory 1986). This is also within the lower range of the values recorded for overt vigilance in other deer populations exposed to carnivores and/or hunters in temperate environments (moose (Alces alces) in Denali National Park, Alaska (Molvar & Bowyer 1994;: c. 10-20%), mule deer (Odocoileus hemionus hemionus) in Northwestern Utah, USA (Altendorf et al 2001: c. 16-40% in juniper forest), roe deer (Capreolus capreolus) in the Aurignac district, France (Benhaiem et al 2008;: c. 25-35%), sika deer (Cervus nippon) in Pengze County, China (Ping et al 2011;: c. 20-30%), but see also: Berger & Cunningham 1988;Laundre et al 2001;Kloppers et al 2005;Lung & Childress 2007;and for other ungulates : Underwood 1982;Bednekoff & Ritter 1994;Crosmary et al 2012; with values c. 10-60%). Vigilance levels observed at our study site were also higher than those observed in elk (Cervus elaphus) in Yellowstone where wolves had been extinct but have been re-introduced.…”
Section: Discussionmentioning
confidence: 99%
“…As such an effect is difficult to exclude in experiments, little effort has been made to accurately assess the quantitative impact of interference on the feeding rates, growth, and survival rates of competing animals, despite evidence of their importance (Schoener 1983). While most studies facing this problem have focused on demonstrating the simultaneous effect of both types of competition (e.g., MacIsaac and Gilbert 1991;Rutten et al 2010), surprisingly, some have implicitly assumed that the effect of exploitation is negligible (e.g., Sutherland and Koene 1982;Ens and Goss-Custard 1984;Stillman et al 2002;Nakayama and Fuiman 2010;Ping et al 2011). However, it is clear that exploitative competition may lead to a gross overestimation of the effect of interference, since the latter phenomenon is prey density dependent (Sutherland and Koene 1982;Vahl et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent efforts to quantify the effects of interference (Gyimesi et al 2010;Nakayama and Fuiman 2010;Rutten et al 2010;Ping et al 2011), little is known about how these effects are influenced by external factors that may be biotic (e.g., prey density) or abiotic (e.g., environmental temperature). Most previous studies-either theoretical (Stillman et al 2000) or empirical (Sih 1981;Dolman 1995;Cresswell 1998;Triplet et al 1999)-support the notion that interference is stronger at lower prey densities (or reduced encounter rates).…”
Section: Introductionmentioning
confidence: 99%